Resepsi Khalayak terhadap Konflik Keluarga dalam Film Ngeri-Ngeri Sedap: Studi Kasus Mahasiswa Angkatan 2020 Program Studi Ilmu Komunikasi Universitas Mulawarman - Putri, Irma Adella; Sucipta, Johantan Alfando Wikanda; Agustian, Jaka Farih; Rohmah, Ainun Nimatu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Movies are part of mass communication and serve as a medium for disseminating information to the public. Movies depict life and contain social stories. Ngeri-Ngeri Sedap is one of Bene Dion's film works that addresses the theme of conflict within a Batak family, reflecting a reality that allows the audience to interpret it in various ways. This research was conducted to analyze how audiences interpret family conflicts in the film Ngeri-Ngeri Sedap. The research uses a qualitative approach method with interviews conducted with five informants selected according to the research criteria. The focus of the research is Stuart Hall's reception theory, dividing interpretations into three categories: dominant hegemonic position, negotiated position, and oppositional position. The data analysis technique used is the Miles and Huberman interactive model data analysis. The results showed that movies still influence audiences in understanding their messages, supported by aspects such as the informants' backgrounds and social lives. The film depicts conflicts between parents and children, such as differences in views on marriage, aspirations, and work. Informants were found to be divided into negotiated and oppositional positions. In the negotiated position, there are informants 3 and 4, which means they understand the movie's meaning but refuse to apply some of its messages. In the oppositional position, there are informants 1, 2, and 5 who reject the family conflict depicted in the movie Ngeri-Ngeri Sedap.